Agricultural soils: A sink or source of methane across the British Isles?. (20th December 2020) - Cowan, Nicholas; Maire, Juliette; Krol, Dominika; Cloy, Joanna M.; Hargreaves, Paul; Murphy, Rachael; Carswell, Alison; Jones, Stephanie K.; Hinton, Nicola; Anderson, Margaret; Famulari, Daniela; Bell, Madeleine J.; et al.
Abstract: This study summarizes a large diverse dataset of methane (CH4 ) fluxes measured from agricultural sites across the British Isles. A total of 53, 976 manual static chamber measurements from 27 different sites were investigated to determine the magnitude of CH4 fluxes from a variety of agricultural fields across the UK and Ireland. Our study shows that contrary to some studies, agricultural soils (both arable and grassland) are small net emitters of CH4 rather than sinks. Mean fluxes measured from arable and grassland sites (excluding fertiliser and tillage events) were 0.11 ± 0.06 and 0.19 ± 0.09 nmol m −2 s −1, respectively, and were not found to be significantly different (Welch t ‐test, p = 0.17). Using the values reported in this study, we estimate that an annual emission of 0.16 and 0.09 Mt of CO2 ‐eq is expected from arable and grassland agricultural soils in the UK and Ireland (comparable to 0.3 and 0.7% of the current annual CH4 emission inventories, respectively). Where CH4 uptake occurs in soils, it is negligible compared to expected emissions of the application of animal manures and tillage events, which were both found to significantly increase CH4 emissions in the immediate few days to months after events. Our study highlights that there are significant differences in CH4 uptake and emissions between sites, and that these differences are partially the result of the moisture content of the soil (i.e., the aerobic status of the soil). We expect uptake of CH4 to be more prevalent in drier soils where volumetric water content does not exceed 35% and emissions to be exponentially greater where agricultural fields become waterlogged. Highlights: This study investigated 53, 976 CH4 flux measurements from 27 sites across the UK Our study shows both arable and grassland soils are small net emitters of CH4 We estimate annual CH4 emissions of 0.16 Mt of CO2 ‐eq from agricultural soils in the UK We estimate annual CH4 emissions of 0.09 Mt of CO2 ‐eq from agricultural soils in Ireland